2021
DOI: 10.3390/ijms22062813
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Apply Water-Deficit Stress: Similarities and Disparities at the Whole Plant Metabolism Level in Medicago truncatula

Abstract: Water-deficit stresses such as drought and salinity are the most important factors limiting crop productivity. Hence, understanding the plant responses to these stresses is key for the improvement of their tolerance and yield. In this study M. truncatula plants were subjected to 250 mM NaCl as well as reduced irrigation (No-W) and 250 g/L polyethylene glycol (PEG)-6000 to induce salinity and drought stress, respectively, provoking a drop to −1.7 MPa in leaf water potential. The whole plant physiology and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 90 publications
(74 reference statements)
3
7
0
Order By: Relevance
“…The accumulation and synthesis of soluble compounds, such as amino acids, particularly proline and soluble sugars, control osmoregulation during drought (Casta ñeda and González 2021). The results of current study showed that both free amino acid and proline concentrations increased in response to drought, which is in agreement with prior research conducted by Du et al (2020b) and Cao et al (2022). This finding supports the notion that increased accumulation of free amino acids and proline is a common response of plants to water deficit conditions.…”
Section: Mt Improved Plant Growth and Water Relation Under Droughtsupporting
confidence: 92%
See 3 more Smart Citations
“…The accumulation and synthesis of soluble compounds, such as amino acids, particularly proline and soluble sugars, control osmoregulation during drought (Casta ñeda and González 2021). The results of current study showed that both free amino acid and proline concentrations increased in response to drought, which is in agreement with prior research conducted by Du et al (2020b) and Cao et al (2022). This finding supports the notion that increased accumulation of free amino acids and proline is a common response of plants to water deficit conditions.…”
Section: Mt Improved Plant Growth and Water Relation Under Droughtsupporting
confidence: 92%
“…The activities of nitrogen metabolism-related enzymes significantly increased when exogenous melatonin (MT) was applied to pepper plants under drought conditions in this study. These findings are consistent with previous research, which has shown that exogenous MT can help to maintain a consistent level of nitrogen assimilation by upregulating significant enzyme activities and offsetting the negative effects of drought on these essential enzyme activities in nitrogen metabolism + (Cao et al 2022). Inorganic N forms such as NH 4 and NO 3…”
Section: Mt Improved Nitrogen Metabolism Under Droughtsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, the identification of these compounds provides a promising connecting link that could bridge the gap between genotype and morpho-physiological traits. As osmotic regulating substances, soluble sugars and soluble protein content are considered as important indicators of the physiological status of plants related to drought tolerance [17,18]. Genes regulating the levels of osmoprotectants are highly stress-responsive and were among the first stressinducible transcripts reported in the literature [19].…”
Section: Introductionmentioning
confidence: 99%